The Dynamic of Teaching Arabic Speaking Skills: A Case Study - Ali Farhan; Maman Abdurahman; Mia Nurmala (CV. Samuel Manurung and Co, 2026)
Students' Arabic language skills can be influenced by the quality of test books, which play a role in supporting student learning. This study examines the maharah al-kalam component in the Arabic textbook for Grade XI students and its implementation in the classroom. The study employed a qualitative case study design and was conducted at SMAIT Al Kahfi in Bogor. The book analyzed referred to MoRA Textbook Evaluation Standards, and its implementation data were collected through classroom observations, interviews, and documentation. The findings show that the content and material aspect scored 44.5%, which is categorized as appropriate. The presentation aspect received 52.5%, also categorized as moderate appropriate. The language aspect achieved 69.1% and was categorized as appropriate. The maharah al-kalam aspect scored 74% and was categorized as appropriate. Besides, the graphical aspect received a perfect score of 100%, categorizing it as highly appropriate. Overall, these results do not fully meet the textbook standards set by MoRA. The successful use of the textbook in Grade XI maharah al-kalam instruction heavily depends on teachers’ ability to apply suitable teaching methods, use various instructional media, and incorporate additional learning materials. Based on these findings, the textbook is still a useful learning resource. However, it needs further development to better address the requirements of Arabic language learning in today’s world